PENGARUH LIKUIDITAS, LEVERAGE DAN PROFIBILITAS TERHADAP LABA BERSIH PADA PERUSAHAAN LQ45 TAHUN 2019-2023 - Qama, Esti (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2025)
This study aims to evaluate the influence of financial ratios, including Return on Assets, Current Ratio, and Debt to Asset Ratio, on net income in consumer goods sector companies listed in the LQ45 index during the 2019–2023 period. The research approach used is quantitative, employing multiple linear regression analysis techniques based on secondary data from official annual financial statements. The findings of the study indicate that both jointly and individually, the three financial ratios do not show a statistically significant effect on the companies’ net income